Optical coherence tomography evaluation of zotarolimus-eluting stents at 9-month follow-up: comparison with sirolimus-eluting stents. Issue 23 (16th June 2009) - Kim, J-S; Jang, I-K; Kim, J-S; Kim, T H; Takano, M; Kume, T; Hur, N W; Ko, Y-G; Choi, D; Hong, M-K; Jang, Y
Abstract : Objective: To evaluate the vascular response at 9 months after zotarolimus-eluting stent (ZES; Endeavor) implantation using optical coherence tomography (OCT). These findings were compared with those after implantation of a sirolimus-eluting stent (SES; Cypher Select). Design: Cross-sectional observational study with prospective OCT registry. Setting: Nine months after ZES or SES implantation. Patients and methods: A total of 68 patients (32 ZES and 36 SES) underwent OCT at 9 months after stent implantation. The neointima hyperplasia (NIH) thickness inside each strut and percentage of NIH area at every 1 mm cross section were measured. Main outcome measurement: The degree of neointimal coverage and the prevalence of malapposition at 9 months after ZES and SES implantation using OCT. Results: The mean (SD) NIH thickness (251.2 (110.0) μm vs 85.5 (53.3) μm, p<0.001) and percentage of NIH area (27.9 (9.1)% vs 11.2 (7.1)%, p<0.001) were significantly greater in ZES than in SES. The prevalence of uncovered strut as well as malapposed strut was significantly lower in ZES than in SES (0.3% vs 12.3%, p<0.001 and 0.08% vs 2.6%, p<0.001). Thrombus was not observed in ZES (0.0% in ZES vs 27.8% in SES, p = 0.001). Conclusions: Neointimal coverage in ZES was almost complete and malapposition was very rare at 9-months' follow-up.